2021
DOI: 10.1051/0004-6361/202141271
|View full text |Cite
|
Sign up to set email alerts
|

First observations and performance of the RPW instrument on board the Solar Orbiter mission

Abstract: The Radio and Plasma Waves (RPW) instrument on the ESA Solar Orbiter mission is designed to measure in situ magnetic and electric fields and waves from the continuum up to several hundred kHz. The RPW also observes solar and heliospheric radio emissions up to 16 MHz. It was switched on and its antennae were successfully deployed two days after the launch of Solar Orbiter on February 10, 2020. Since then, the instrument has acquired enough data to make it possible to assess its performance and the electromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The Type III burst was succeeded by a Type II burst, observed by PSP, STEREO-A, and Wind (refer to Figure A2(a)-Asd). The heightened noise level at Solar Orbiter led to the nondetection of the Type II burst (Maksimovic et al 2021). To pinpoint the Type III burstʼs location in interplanetary space (illustrated in Figure A2(e)), we employed two distinct methodologies.…”
Section: Appendix B Interplanetary Radio Burst Measurements and Conne...mentioning
confidence: 99%
“…The Type III burst was succeeded by a Type II burst, observed by PSP, STEREO-A, and Wind (refer to Figure A2(a)-Asd). The heightened noise level at Solar Orbiter led to the nondetection of the Type II burst (Maksimovic et al 2021). To pinpoint the Type III burstʼs location in interplanetary space (illustrated in Figure A2(e)), we employed two distinct methodologies.…”
Section: Appendix B Interplanetary Radio Burst Measurements and Conne...mentioning
confidence: 99%
“…The spacecraft (SC) body separates the antenna ports, creating a gap between the arms of each dipole of 2 d = 2.98 m, a length comparable to L ant . Configurations that feature the gap operate only on PSP FIELDS (Bale et al., 2016) and Solar Orbiter Radio and Plasma Waves (RPW) (Khotyaintsev et al., 2021; Maksimović, Bale, Chust, et al., 2020; Maksimovic et al., 2021) instruments, and initial observations showed that the total electron density could be inferred by locating the peak of the signal at fpne ${f}_{p}\sim \sqrt{{n}_{e}}$ (Bale et al., 2019). However, the shape of the observed QTN spectra cannot be modelled by the ARFs derived for the case of dipoles without a gap (Kuehl, 1966, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…The spacecraft (SC) body separates the antenna ports, creating a gap between the arms of each dipole of 2d = 2.98 m, a length comparable to L ant . Configurations that feature the gap operate only on PSP FIELDS (Bale et al, 2016) and Solar Orbiter Radio and Plasma Waves (RPW) (Khotyaintsev et al, 2021;Maksimović, Bale, Chust, et al, 2020;Maksimovic et al, 2021) instruments, and initial observations showed that the total electron density could be inferred by locating the peak of the signal at 𝐴𝐴 𝐴𝐴𝑝𝑝 ∼ √ 𝑛𝑛𝑒𝑒 (Bale et al, 2019). However, the shape of the observed QTN spectra cannot be modelled by the ARFs derived for the case of dipoles without a gap (Kuehl, 1966(Kuehl, , 1967.…”
Section: Introductionmentioning
confidence: 99%